In situ research on temperature dependence of the lattice parameters of fusible metals in thin Cu-Pb and Cu-Bi films - Dukarov, S.V.; Petrushenko, S.I.; Sukhov, V.N.; Skryl, O.I. (Functional Materials, 2016)
Results of in situ electron diffraction study on temperature dependence of the lattice parameter of fusible component in Cu-Pb and Cu-Bi two-layer films are presented. It is found that at the room temperature, the parameters of Pb and Bi crystal lattices are agreed with the tabular data, however, with temperature increasing one can observe the deviation from the values corresponding to bulk samples. This indicates a significant increase of solubility of the components in the films under study. In the Cu-Pb films according to the estimation made by assuming a linear dependence of the lattice parameter of the solid solution from concentration, copper solubility in the solid lead at near the eutectic temperature is about 0.8 at.%, which is much greater than the value known for the bulk samples.